Savings in Singapore - Ng, Stella (2014)
Singapore's savings rate is among the highest in the world. The high rates have been attributed to the compulsory saving to the Central Provident Fund. This paper examines the savings behaviour of Singapore, in particular, the voluntary private savings. Voluntary savings make up a considerable portion of gross domestic savings, hence rendering its importance. Unlike CPF saving, which is determined by the Government, the voluntary component of saving is influenced by other factors that are beyond Government control. Based on empirical tests, Singapore's voluntary private savings behaviour is best explained by the Permanent Income theory of savings. It is found that CPF savings have a negative influence on voluntary private savings. However, the former is not a perfect substitute of voluntary savings.